Indigenous Cultures and Sustainable Development in Latin America - MacNeill, Timothy (Springer International Publishing : Imprint: Palgrave Macmillan, 2020)
This open access book outlines development theory and practice over time as well as critically interrogates the "cultural turn" in development policy in Latin American indigenous communities, specifically, in Guatemala, Honduras, Ecuador, and Bolivia. It becomes apparent that culturally sustainable development is both a new and old idea, which is simultaneously traditional and modern, and that it is a necessary iteration in thinking on development. This new strain of thought could inform not only the work of development practitioners, graduate students, and theorists working in the Global South, but in the Global North as well. Timothy MacNeill is Associate Teaching Professor of Political Science and Program Director of Sustainability Studies at University of Ontario Institute of Technology, Canada.